PREFERENSI DIGITAL AUDIO WORKSTATION (DAW) DAN PENGARUHNYA TERHADAP GAYA ESTETIKA MAHASISWA MINAT STUDI MUSIK TEKNOLOGI - Jaohari, Enry Johan; Karyono, Tri; Sukmayadi, Yudi; Purwanto, Andrian (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2025)
AbstractThis study explores the preference for Digital Audio Workstation (DAW) and its influence on the musical aesthetics of students majoring in Music Technology. Employing a qualitative descriptive approach with a practice-based research framework, the research involved active students at the Music Study Program, School of Art and Design Education, Universitas Pendidikan Indonesia. Data were collected through open-ended questionnaires, semi-structured interviews, and documentation of students’ digital music works. The findings reveal that DAW selection is influenced by a combination of technical, pedagogical, and creative factors, with Studio One being the most preferred. The features most utilized by students include mixing effects, MIDI sequencing, and preset plugins. Approximately one-third of the students acknowledged that DAW significantly impacted the structure and aesthetic style of their works, while others emphasized personal identity over technological influence. These results indicate that DAWs act not only as production tools but also as mediators of musical thought and expression. The study suggests the necessity of pedagogical frameworks that encourage both technical proficiency and critical reflection in digital music education. The findings also highlight the need for curriculum development that provides students with diverse DAW platforms to support artistic exploration and identity formation. Key Words DAW, music technology, musical aesthetics, digital creativity, music education AbstrakPenelitian ini bertujuan untuk mengeksplorasi preferensi penggunaan Digital Audio Workstation (DAW) dan pengaruhnya terhadap estetika musikal mahasiswa aktif Program Studi Musik yang mengambil Minat Studi Musik Teknologi. Pendekatan yang digunakan adalah kualitatif deskriptif dengan kerangka practice-based research. Data dikumpulkan melalui angket terbuka, wawancara semi-terstruktur, dan dokumentasi karya musik digital mahasiswa. Hasil penelitian menunjukkan bahwa pemilihan DAW dipengaruhi oleh kombinasi faktor teknis, pedagogis, dan kreatif, dengan Studio One menjadi platform yang paling dominan. Fitur yang paling sering digunakan mahasiswa meliputi efek mixing, editor MIDI, dan preset plugin. Sekitar sepertiga mahasiswa mengakui bahwa DAW berkontribusi signifikan dalam membentuk struktur dan gaya estetika karya mereka, sedangkan sebagian besar lainnya menilai bahwa identitas musikal pribadi lebih berpengaruh. Temuan ini menunjukkan bahwa DAW berperan tidak hanya sebagai alat produksi, tetapi juga sebagai mediator dalam berpikir dan mengekspresikan ide musikal. Penelitian ini merekomendasikan pengembangan kurikulum musik digital yang menyeimbangkan penguasaan teknis dengan refleksi kritis terhadap penggunaan teknologi. Kata Kunci DAW, teknologi musik, estetika musikal, kreativitas digital, Pendidikan musik.